Common Neuroginic Bladder Disorder due to Spinal Cord Injuries - A Review - Ullah, ATM A; Hasan, MS; Hossain, TMS; Rahman, MS (Bangladesh Journal of Urology, 2012)
Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.31-34